2011
DOI: 10.1371/journal.pone.0023340
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating Grotesque from Typical Faces: Evidence from the Thatcher Illusion

Abstract: The discrimination of thatcherized faces from typical faces was explored in two simultaneous alternative forced choice tasks. Reaction times (RTs) and errors were measured in a behavioural task. Brain activation was measured in an equivalent fMRI task. In both tasks, participants were tested with upright and inverted faces. Participants were also tested on churches in the behavioural task. The behavioural task confirmed the face specificity of the illusion (by comparing inversion effects for faces against chur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Furthermore, we have recently shown that the efficacy of the illusion relies on a network of areas involved in social and emotional processing and which are engaged in mentalizing, including the medial prefrontal (mPFC)/orbitofrontal cortex and the posterior cingulate/precuneus. Discrimination between a typical face and a thatcherized face led to increased activation in the face-processing network when the faces were presented inverted [21]. Studies investigating face processing in normal inverted faces have yielded discrepant results.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, we have recently shown that the efficacy of the illusion relies on a network of areas involved in social and emotional processing and which are engaged in mentalizing, including the medial prefrontal (mPFC)/orbitofrontal cortex and the posterior cingulate/precuneus. Discrimination between a typical face and a thatcherized face led to increased activation in the face-processing network when the faces were presented inverted [21]. Studies investigating face processing in normal inverted faces have yielded discrepant results.…”
Section: Introductionmentioning
confidence: 95%
“…Our previous work in a neurotypical population demonstrated the pre-eminent role of the eyes in generating the TI [21]. When looking at faces, adults with neurotypical development have a natural tendency to attend more to the eye region [25], and this is not the case in individuals with ASD [2], [3], [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These earlier studies have been numerous and the relevance to people relationships highlighted (e.g., Donnelly et al, 2011;Mestry et al, 2011Utz & Carbon, 2016). However, a study of the relationships among visual processing features, age and familiarity in the one project, could, we hoped, add new information and understanding of how the decline occurs and could lead to new procedures that help reduce the decline and its effects.…”
Section: Assessment Of Visual Processing: the Thatcher Studiesmentioning
confidence: 92%
“…These earlier researchers, beginning with Thompson (1980), used normal and "Thatcherised" images (faces with distorted elements) mostly images of celebrity faces (e.g., Julia Roberts's face), but none had combined both in the one study to our knowledge (see also Utz & Carbon, 2016). The faces are usually presented inverted or upright in conjunction with feature distortions (e.g., Bartlett & Searcy, 1993;Carbon & Leder, 2005;Donnelly, Cornes, & Menneer, 2012;Donnelly et al, 2011;Milivojevic, Clapp, Johnson, & Croballis, 2003;Rakover, 1999;Tanaka, Kaiser, Hagen, & Pearce, 2014;Valentine, 1988;Xu & Tanaka, 2013).…”
Section: Assessment: the Thatcher Illusion-our Study's Approachmentioning
confidence: 99%